1996
DOI: 10.1021/ic9414280
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of the Reaction between Serum Albumin and Auranofin (and Its Isopropyl Analogue) in Vitro

Abstract: The first detailed kinetic study of in vitro reactions between serum albumin and the secondgeneration gold drug 3,4,glucopytanosato-S-) gold(I)] and its tri-i-propylphosphine analogue, .iPr3PAuSATg, are reported. The reactions were investigated using Penefsky spun columns and NMR saturation transfer kinetics.Based on the Penefsky column data, the binding of the Et3PAuSATg to AIbSH (0.600 mM) was complete when gold concentrations were limiting: 0.093, 0.151, and 0.225 mM. The reaction is biphasic. The fast phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
36
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 38 publications
4
36
0
2
Order By: Relevance
“…Both deacetylated auranofin and the parent [AuCl(PEt 3 )] complex form the same [(Et 3 P)Au(S-alb)] adduct by displacement of the anion. By studying reactions with auranofin instead of the unstable deacetylated form, under conditions approximating those in vivo, such adduct formation is of the first-order in auranofin with a rate constant of 2.9 ± 0.2 s -1 [6]. These data support the view that auranofin (or its deacetylated metabolite)…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…Both deacetylated auranofin and the parent [AuCl(PEt 3 )] complex form the same [(Et 3 P)Au(S-alb)] adduct by displacement of the anion. By studying reactions with auranofin instead of the unstable deacetylated form, under conditions approximating those in vivo, such adduct formation is of the first-order in auranofin with a rate constant of 2.9 ± 0.2 s -1 [6]. These data support the view that auranofin (or its deacetylated metabolite)…”
Section: Introductionsupporting
confidence: 67%
“…should have a very short lifetime after entering the bloodstream where albumin is present in excessive amount fold) compared to the gold drug [6]. To corroborate this hypothesis, Christodoulou et al [7] reported a conformational change in albumin that accompanies gold binding to cys-34.…”
Section: Introductionmentioning
confidence: 98%
“…[19,44] Moreover, investigation of the reactions of auranofin with serum albumin showed that, upon gold binding to Cys34, the thioglucose ligand was displaced with the phosphine moiety remaining attached. [45] A similar mechanism of thiolate release may be responsible for the activity of the series of gold(I) compounds described here. Further studies are underway to establish whether TrxR histidines could also form covalent interactions with gold ions and to determine the nature of the protein-bound metallofragments.…”
mentioning
confidence: 65%
“…13 Thiol-ligand exchange reactions have been reported by various authors demonstrating the role of ligand exchange of gold compounds in different situations. 12,13,[24][25][26] Ligand exchange reactions with the complexes that have an easily accessible chlorine atom such as 1b, 2b, 3b, 4b, 5, 7 and 8 might therefore have been favoured as all these gold complexes inhibited RT. It is also possible that the gold compounds intercalate in the DNA molecule being formed in the reaction mixture of enzyme and nucleotides, thereby interfering with the reverse transcription reaction catalysed by RT.…”
Section: Discussionmentioning
confidence: 99%